Exploiting noncovalent interactions for room-temperature heteroselective rac-lactide polymerization using aluminum catalysts - Gesslbauer,S; Savela,R; Chen,Y; White,AJP; Romain,C (ACS Catalysis, 2019)
Whereas harnessing noncovalent interactions (NCIs) has largely been applied to late-transition-metal complexes and to the corresponding catalytic reactions, there are very few examples showing the importance of NCIs in early-transition-metal and main-group-metal catalysis. Here, we report on the effects of hydrogen bond donors in the catalytic pocket to explain the high activity and stereoselectivity of a series of aluminum catam complexes in rac-lactide ring-opening polymerization (ROP). Four original aluminum catam catalysts have been synthesized and fully characterized. Structure–activity relationships and isotope effects show the importance of the NH moieties of the ligand in rac-lactide ROP. Computational studies highlight beneficial hydrogen bonds between the ligand and the monomer. Overall, structural characterization of the catalysts and mechanistic, kinetic, and computational studies support the benefits of noncovalent interactions in the catalytic pocket.